Pengembangan Bahan Ajar Audiovisual Berbasis Contextual Teaching and Learning (CTL) pada Materi Cerita Pendek di Kelas XI SMA Negeri 14 Medan - Desra Nita Tampubolon (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to develop audiovisual teaching materials based on Contextual Teaching and Learning (CTL) on Short Story Materials at SMA Negeri 14 Medan. The population of this study is class XI at SMA Negeri 14 Medan with a sample of 34 students. This research is a Research and Development (RnD) using the Borg and Gall model with stages 1) Potential and problems, 2) Data collection, 3) Product design, 4) Design validation, 5) Design revision, 6) Product trial, 7) Product revision, 8) Usage trial. After being carried out step by step, the validity test of the media of material experts is as many as 81% and media experts as many as 97% with the percentage results strongly agreeing to be used in the field (very feasible). Meanwhile, the assessment from students was 86.64% and Indonesian teachers were 96 with the category of suitable for use in the field. This research produces teaching materials in the form of audiovisual (audio and video) based on Contextual Teaching and Learning on short story materials.